Estudio de factibilidad para la creación del producto limpiador multiuso Bioclean en la ciudad de Barranquilla (2014)
AMBBIO COLOMBIA S.A.S. is a family enterprise located in Barranquilla, Colombia with more than 15 years on the national market, dedicated to the care and improvement of the environment by means of the bioengineering. The company is specializing in the microorganisms handling descontaminantes which it uses for to design and to provide solutions in the following fields: The treatment of wastes water (servants and industrialists) The water purification The bioremediación (biological recovery) of contaminated soils The dumps treatment AMBBIO COLOMBIA SAS was founded by José Víctor Dugand Arguello, pioneer in Colombia in the handling of the microorganisms who has realized projects with entities governmental, companies of energy, companies in the industry of the oil, the sector of I steel, cement, breweries, hospitals, hotels and social clubs